Students as Causal Agents: Engagement in Course Selection - Haarstad, Cathy; Borisinkoff, Evan; Weathers, Rhonda (Journal of the American Academy of Special Education Professionals, 2021)
While significant evidence indicates that making complex choices and decisions contributes to self-determination, the authors found no studies to date in which the phenomenon of engaging students with disabilities in choosing their high school courses was examined as a dependent variable. This phenomenological study explored how course-selection might serve as a means of enabling self-determination, which contextual factors might influence student engagement in course selection and how students with disabilities typically participate in course-selection. The main findings point to the high readability demands of many high-school course descriptions and established proof-of-concept on the feasibility of having a small (n=15) group of students with autism and developmental disabilities use a newly developed website to select courses and share preferences. Recommendations for improving the site as well as suggestions for further research are included.